Electrical Conductivity in Fibrous Composites (Adv. Phys. Res. 8/2025) - Hunter, Luke; Bertazzo, Sergio (Advanced Physics Research, 2025)
Spanning Clusters and Electrical Conductivity When fibers are added to a material, isolated clusters begin to interconnect. Once a critical fiber density is reached, a system‐spanning network emerges, visibly highlighted here in electric blue, that enables long‐range charge transport and determines the material's electrical conductivity. See Research Article 2500040 by Luke Hunter and Sergio Bertazzo for more details.